Colonial Ideologies at Theophilus Waldmeier’s Asfuriyeh Mental Hospital in Ottoman Lebanon 1896-1909 - Bergman, Taru (My University, 2024)
In my master’s thesis I research the quaker asylum Asfuriyeh in Ottoman Lebanon. I focus on the early years of the asylum, especially focusing on its’ founder, Theophilus Waldmeier. I posit that his specific ideologies, religious and otherwise, were the main building block for this asylum. I explore how the orientalist worldview affected how the westerners, especially Asfuriyeh’s founder Theophilus Waldmeier, and the doctors of the asylum, saw and described the patients. I mainly focus on the contents of the yearly reports, published for the donors of the asylum. Additionally the unpublished manuscript of Theophilus Waldmeier’s memoirs was used to supplement the materials. To support my research, I used classic literature on these subjects, such as Edward Said’s Orientalism and Michel Foucault’s Madness and Civilization, with appropriate critiques for the more controversial aspects to these works. I posit in this thesis that despite the benevolent missionary beginnings, these yearly reports showed clear examples of colonial exertions of power, and orientalist ideology. I conclude that Asfuriyeh was indeed colonial in ideology, and in function.
Keywords: Colonialism, Orientalism, Lebanon, Quakers, Asylum, Mental illness, Theophilus Waldmeier